Genome Sequences of 15 Gardnerella vaginalis Strains Isolated from the Vaginas of Women with and without Bacterial Vaginosis - Robinson, Lloyd S. (Genome Announc, 2016)
Gardnerella vaginalis is a predominant species in bacterial vaginosis, a dysbiosis of the vagina that is associated with adverse health outcomes, including preterm birth. Here, we present the draft genome sequences of 15 Gardnerella vaginalis strains (now available through BEI Resources) isolated from women with and without bacterial vaginosis.